POLITENESS STRATEGY IN REQUEST: DOES IT ALWAYS WORK WELL? - Diah Ikawati Ayuningtyas (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2012)
Request is one of speech act phenomena, which we encounter most frequently in everyday social interaction. When expressing a request, the speaker has an intention to the hearer to do something that is beneficial to him/her. In this circumstance, the speaker is impossing on the hearer; while the hearer has to pay cost of carrying out the request. Brown and Levinson claim request as one kind of face threatening acts (FTA). Because of the nature of request, politeness strategy must be applied when expressing a request. There are four super strategies of politeness strategy defined by Brown and Levinson, i.e. bald on record, positive politeness, negative politeness, as well as off record. There are some reasons underlying the use of certain strategies. They are the urgency of the request itself, the relationship between the speaker and the hearer, not to mention the speaker’s willingness to lessen the imposition on the hearer. Yet, the use of the politeness strategies do not always work well. In other word, the speaker does not always gain what he wants.